Constitutive hippocampal cholesterol loss underlies poor cognition in old rodents. Issue 7 (30th May 2014) - Martin, Mauricio G; Ahmed, Tariq; Korovaichuk, Alejandra; Venero, Cesar; Menchón, Silvia A; Salas, Isabel; Munck, Sebastian; Herreras, Oscar; Balschun, Detlef; Dotti, Carlos G
Abstract Cognitive decline is one of the many characteristics of aging. Reduced long‐term potentiation (LTP) and long‐term depression (LTD) are thought to be responsible for this decline, although the precise mechanisms underlying LTP and LTD dampening in the old remain unclear. We previously showed that aging is accompanied by the loss of cholesterol from the hippocampus, which leads to PI3K/Akt phosphorylation. Given that Akt de‐phosphorylation is required for glutamate receptor internalization and LTD, we hypothesized that the decrease in cholesterol in neuronal membranes may contribute to the deficits in LTD typical of aging. Here, we show that cholesterol loss triggers p‐Akt accumulation, which in turn perturbs the normal cellular and molecular responses induced by LTD, such as impaired AMPA receptor internalization and its reduced lateral diffusion. Electrophysiology recordings in brain slices of old mice and in anesthetized elderly rats demonstrate that the reduced hippocampal LTD associated with age can be rescued by cholesterol perfusion. Accordingly, cholesterol replenishment in aging animals improves hippocampal‐dependent learning and memory in the water maze test.